Genome-wide association study of blood pressure and hypertension - Levy, Daniel; Ehret, Georg B; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Dehghan, Abbas; Glazer, Nicole L; Morrison, Alanna C; Johnson, Andrew D; Aspelund, Thor; Aulchenko, Yurii; Lumley, Thomas; et al. (Nature genetics, 2009)
Daniel Levy and colleagues report a meta-analysis of genome-wide association studies for blood pressure traits as part of the CHARGE consortium, reporting eight loci with replicated association to systolic and/or diastolic blood pressure, with one of these loci also associated to hypertension. Blood pressure is a major cardiovascular disease risk factor. To date, few variants associated with interindividual blood pressure variation have been identified and replicated. Here we report results of a genome-wide association study of systolic (SBP) and diastolic (DBP) blood pressure and hypertension in the CHARGE Consortium ( n = 29,136), identifying 13 SNPs for SBP, 20 for DBP and 10 for hypertension at P < 4 × 10 −7 . The top ten loci for SBP and DBP were incorporated into a risk score; mean BP and prevalence of hypertension increased in relation to the number of risk alleles carried. When ten CHARGE SNPs for each trait were included in a joint meta-analysis with the Global BPgen Consortium ( n = 34,433), four CHARGE loci attained genome-wide significance ( P < 5 × 10 −8 ) for SBP ( ATP2B1, CYP17A1, PLEKHA7, SH2B3 ), six for DBP ( ATP2B1, CACNB2, CSK-ULK3, SH2B3, TBX3-TBX5, ULK4 ) and one for hypertension ( ATP2B1 ). Identifying genes associated with blood pressure advances our understanding of blood pressure regulation and highlights potential drug targets for the prevention or treatment of hypertension.